Synthesis, characterization and application of crystalline organic-inorganic hybrid materials - Teng, Wen Yuan (2014)
Titanium dioxide (TiO2) is currently one of the best suited semiconductor photocatalysts for industrial applications due to its efficient photoactivity, high stability, low cost and safety of use. This has led to the use of TiO2 in many environmental applications such as self-cleaning surfaces, air cleaning, water treatments, self-sterilisation and its intense research in water splitting. However, the large band gap of TiO2 limits its photoresponse to the ultraviolet (UV) region, which accounts for only about 3-5% of the solar spectrum. Therefore, TiO2¬ is unable to efficiently harness solar energy for its applications and its practical use has been limited. Here, we report the synthesis of a new Ti (IV)-based porous metal-organic framework (NTU-9) with one-dimensional nano-sized channel. NTU-9 displays strong absorption in the visible region and has a band gap of 1.72eV, allowing it to absorb visible light. In addition, photoelectrochemical tests reveal that NTU-9 is a p-type semiconductor and responses to visible light illumination with wavelength longer than 400nm. Moreover, NTU-9 is capable of photocatalytic degradation of organic dyes under visible light and is stable even after several repeated cycles. This work demonstrates the potential application of Ti (IV)-based metal organic frameworks (MOFs) in the development of efficient visible light photocatalyst.